Analisis Keterkaitan Manusia dan Agama dalam Kehidupan Sosial - Anjani, Mauly Lovika; Ananda, Syaira; Lubis, Siti Nur Annisa Yuizati; Soleha, Pratiwi; Rozi, Mhd. Fakhur (Mahad Aly Al Fithrah, 2025)
Human social life is inseparable from the influence of religious values that shape ways of thinking, behavior, and interpersonal relationships within society. This study aims to analyze how religion contributes to the formation of social ethics, collective identity, and cohesion in a pluralistic society. Using a descriptive qualitative approach, the research relies on document analysis and direct observation of religious-social practices in both urban and semi-urban communities. The findings reveal that religion plays a central role as a source of moral values, a foundation for social solidarity, and a bridge for intergroup communication. However, when interpreted narrowly and exclusively, religion also holds the potential to trigger social segregation. Therefore, an inclusive and humanistic understanding of religion is essential to ensure that its social functions remain relevant in promoting harmony and social justice.